Behavior problems in elementary and preschool : prevalence, attitudes & resources - Dagný Hermannsdóttir 1985- (2017)
Behavior problems are common both in elementary and preschools, and frequently cause disruption in education for other students, teachers, administrators and parents. Behavior problems is reported by teachers to be their single highest concern and is the knowledge of the cause important so it is possible to diagnose the problem as soon as possible. The main aim of this study was to examine the prevalence of behavior problems in elementary and preschool as well the resources teachers have and how well prepared they are in dealing with behavior problems. A questionnaire was sent to all elementary and preschool teachers in Iceland. Participants were 128 elementary teachers and 121 preschool teachers. The participants completed a questionnaire through a survey link which was sent by an e-mail. Consistent with previous research we found that teachers often deal with behavior problem both in elementary and in preschool. In addition, a majority of elementary and preschool teachers reported that they would like more help dealing with behavior problem than they are currently getting. The results underline the importance of knowledge of the cause and for teachers to know how to deal with the problematic behavior. Keywords: Psychology, Children, Problem behavior, Elementary school, Preschool, Prevalence Hegðunarvandi er algengur bæði í grunnskólum og leikskólum og valda oft miklum truflunum fyrir nemendur, kennara, stjórnendum og foreldra. Hegðunarvandamál eru eitt af helstu áhyggjuefnum kennara og er þekking á orsökum mikilvægt svo að hægt sé að greina vandamálið eins fljótt og auðið er. Markmið þessarar rannsóknar var að kanna algengi hegðunarvandamála í grunnskólum og leikskólum, auk færni kennara og hversu vel undirbúnir þeir eru til þess að takast á við hegðunarvanda. Spurningalisti var sendur til allra grunn- og leikskólakennara á Íslandi. Þátttakendur voru 128 grunnskólakennarar og 121 leikskólakennarar. Þátttakendur svöruðu spurningalista í gegnum könnunartengil sem var sendur með tölvupósti. Í samræmi við fyrri ...